Investigation of Dielectric Properties of Polymers and their Discrimination Using Terahertz Time-Domain Spectroscopy with Principal Component Analysis. Issue 3 (March 2017) - Mumtaz, Muhammad; Mahmood, Ahsan; Khan, Sabih D.; Zia, M. Aslam; Ahmed, Mushtaq; Ahmad, Izhar
Polymers are among the most commonly used materials in our everyday life. They are generally transparent to terahertz (THz) radiation, but are quite difficult to differentiate using optical techniques as few or no characteristic features exist in the spectral range of <2.0 THz for small and portable radiation systems. In this work, we report experimental measurement of refractive indices and absorption coefficients of styrene acrylonitrile (SAN) and Bakelite in the spectral range of 0.2–2.0 THz for the first time. Additionally, we demonstrate that by combining principle component analysis (PCA) with THz time-domain spectroscopy one can differentiate such polymers. In this analysis, the first three principle components PC1, PC2, and PC3 depict >94% variance with a distribution of 72.45%, 11.52%, and 9.38%, respectively.